2015
DOI: 10.1007/s10035-015-0596-7
|View full text |Cite
|
Sign up to set email alerts
|

A composite particle model for non-spherical particles in DEM simulations

Abstract: This paper presents a composite particle model with sphere clumps for modelling non-spherical particles in discrete element method (DEM) simulations. The formulation of the sphere clumps uses random selections of particle radii and positions, thus it can theoretically simulate all possible non-spherical particles encountered in engineering projects. In this study, the generation of sphere clumps in space was discussed in detail, and different particle nonsphericities were compared. This numerical model has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…The tests using granular mixture exhibit an intermediate trapping efficiency because the existence of spherical particles can increase the overall mobility of granular flow. The dynamics of particle clumps can match well with the observation in Zhao et al (2015) that the shear resistance of a granular assembly increases with the non-sphericity of the constituent particles.…”
Section: Trapping Efficiencysupporting
confidence: 79%
“…The tests using granular mixture exhibit an intermediate trapping efficiency because the existence of spherical particles can increase the overall mobility of granular flow. The dynamics of particle clumps can match well with the observation in Zhao et al (2015) that the shear resistance of a granular assembly increases with the non-sphericity of the constituent particles.…”
Section: Trapping Efficiencysupporting
confidence: 79%
“…ratio of maximum to minimum length) and found that the angle of shearing resistance decreases as the particle elongation increases for samples with the same initial density. Zhao et al [14] used a composite (clumped) particle model to create non-spherical particles and demonstrated that particle shape increased resistance to compaction. Kumari and Sitharam [15] studied the effect of particle aspect ratio on the monotonic shear behavior, but their study was limited to granular assemblies with only two aspect ratios but it must be highlighted that the particle grading of these DEM specimens was not unique.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that QH-E lunar soil simulant is of angular shape with sharp corners and a highly irregular surface because of the Raymond mill method used to grind QH-E [24]. In the tri-axial compression tests, the irregular particle shape can increase the shear strength [11,30]. Therefore, the simulated values of peak deviatoric stress, residual stress and axial strain at peak stress are slightly smaller than those of experimental results.…”
Section: Tab 1 -Parameters For Pfc Tri-axial Compression Numerical Smentioning
confidence: 94%